Sequential Card Activities of Recollect Experience for Elderly with Dementia - Fang Lin Chao; Boxiu Fanjiang (Advances in Science, Technology and Engineering Systems Journal, 2018)
In this study, the authors propose a modified design of sequential card activities to recollect experience for the elderly with Dementia. The cards and App were designed to complement each other for Nostalgia-based support. Image and text are utilized to trigger memories that bring out shared experience from the patient. By using suitable trigger elements, group sharing, and physical objects, one can enhance the memory recall. The procedure of rice dumpling preparation and making were listed in a sequential step and printed on cards. Cards are shuffled, and the elderly are asked to sort these cards to right sequence with the help of QR scanner. In multiple theme scenarios, different groups of object making steps were mixed, and the player needs to select cards that related to a specific group. Using actual items and activities, the triggered of elder’s experience was confirmed. The qualitative testing results showed that the elderly enjoyed the activities. Those events verified the effectiveness of the proposed method.
Keywords: Sequential card; Dementia; QR code; App